IMPLEMENTATION OF IN-GROUP COUNSELING CAREER CHOICE COACHING IN MAN 1 MEDAN STUDENTS: IMPLEMENTASI KONSELING KELOMPOK DALAM PEMBINAAN PEMILIHAN KARIR PADA SISWA MAN 1 MEDAN - Yanti, Novi (UPMI Proceeding Series, 2023)
The implementation of career selection guidance cannot be separated from comprehensive guidance. Career guidance now has its own place, so it is often carried out. Career guidance for students functions as selecting a study program, working according to the study program they choose, preparing human resources for development, so that they need the best possible preparation to face the future, jobs, positions that are in accordance with the potential that exists in each of them. -each. Based on the results of observations and interviews with students in class The implementation of guidance and counseling still does not provide a good explanation of students' future career choices related to the education they are currently undertaking. The implementation of guidance and counseling, especially career guidance, still does not touch on student career development and selection. The research method used in carrying out this research is a qualitative method, namely research that uses a natural setting with the aim of interpreting the phenomena that occur and is carried out by involving various existing methods. Implementation of group counseling with career guidance preparation steps, career guidance implementation steps and career guidance evaluation steps. Student behavior can be seen from the student's ability to express career choices that are in accordance with the student's ability to express career choices that are in accordance with his ability to express career choices that suit his abilities for the benefit of a better future.